DOES FIRM VALUE MATTER? EMPIRICAL EVIDENCE FROM INDONESIA - Putro, Guruh Marhaenis Handoko; Imawan, Amrizal; Megasyara, Ira; Febrianti, Devi (UIN Sunan Gunung Djati Bandung, 2024)
The COVID-19 pandemic has hurt the entire government and corporate financial system, making it difficult for businesses to distribute dividends. During the COVID-19 epidemic, this study examines the possible impact of financial statements on firm value by considering dividend policy as a moderating factor. This research employs a quantitative methodology, utilizing purposive sampling techniques and secondary data. The sample data includes all public companies listed on the Indonesia Stock Exchange between 2020 and 2022. There are 127 sample data. We conducted the test using SmartPLS software. Researchers looked at three financial parameters: profitability, leverage, and liquidity. The research results show that leverage and profitability, not liquidity, can influence firm value. The impact of dividend policy on the relationship between profitability and company value is evident, while it does not affect leverage or liquidity. To identify this problem accurately, the researchers used signal theory to get accurate results in identifying this problem. We hope the research results will alert investors to exercise caution when purchasing shares, particularly in manufacturing companies.